Obesity in pregnancy - Cabrera Ramos, Santiago (2025)
The pathophysiology of obesity includes adipose tissue dysfunction, alterations inadipokine secretion and chronic inflammation, which contribute to insulin resistance.During pregnancy, this increases the risk of complications such as gestationaldiabetes, preeclampsia, miscarriage, premature delivery and fetal death. In addition,obesity is linked to an increased risk of cesarean section, anesthetic complications,postoperative infections and venous thromboembolism. Management of obesityin this setting focuses on behavioral and lifestyle interventions, limiting excessiveweight gain. The use of weight-reducing medications is contraindicated, whilebariatric surgery may be an option if performed in the preconceptional state.